Effects of forest age and stand density on the growth, soil moisture content, and soil carbon content of Populus simoni plantations in the sandy area of western Liaoning, Northeast China - Hao Chen; Zhaowei Zhang; Xiangyu Yang; Xin Ai; Yutao Wang; Ping Liu (Scientific Reports)
Abstract Poplar (Populus simoni) plantations are crucial in the sandy regions of western Liaoning, serving key roles in wind protection, sand stabilization, soil moisture regulation, and carbon sequestration. However, challenges such as suboptimal stand quality and limited ecological benefits persist. This study aims to elucidate the growth dynamics of poplar plantations and their impact on soil moisture content and soil carbon content in this region. We established 75 standard plots across various age groups and stand densities in Fuxin City, measuring poplar diameter at breast height (DBH), tree height (TH), soil moisture content, and soil carbon content. We found that DBH and TH increase with increasing stand density in young and middle-aged forests, but the opposite is true at near-maturity, maturity, and over-maturity, where DBH and TH decrease with increasing stand density. Soil moisture content rises with stand density in younger forests, while soil carbon content increases with age, with surface soil layers exhibiting higher carbon concentrations. The soil carbon stock in these plantations is approximately 3.0 × 106 tons, the highest recorded in Fuxin City. This research provides a foundation for the effective management and development of poplar plantations in wind-prone, sandy areas. Overall, optimizing stand density and managing forest age distribution are essential for enhancing the ecological and carbon sequestration benefits of poplar plantations in this region.